Elevated D-glucose induces insulin insensitivity in human umbilical endothelial cells isolated from gestational diabetic pregnancies - Sobrevia, L (Blackwell Science Inc, 1998)
1. The effects of human insulin and elevated D-glucose on L-arginine transport and synthesis of nitric oxide (NO) and prostacyclin (PGI(2)) have been investigated in human umbilical vein endothelial cells isolated from gestational diabetic pregnancies. 2. The increase in the V(max) for L-arginine transport (9.0 ± 1.1 pmol (μg protein)(−1) min(−1)) in diabetic endothelial cells cultured in 5 mm D-glucose was unaffected following 24 h exposure to 25 mm D-glucose. 3. Gestational diabetes-induced increases in basal intracellular cGMP and L-citrulline levels (inhibitable by L-NAME) and [Ca(2+)](i) were unaffected by elevated D-glucose. In contrast, PGI(2) release was inhibited in diabetic cells exposed to either 5 or 25 mm D-glucose. 4. Elevated D-glucose attenuated histamine (10 μM, 5 min)-stimulated accumulation of cGMP and L-citrulline in endothelial cells isolated from gestational diabetic pregnancies. 5. The membrane hyperpolarization (-79 ± 0.9 mV) sustained in diabetic endothelial cells in culture was insensitive to elevated D-glucose. 6. Elevated D-glucose abolished the stimulatory effect of human insulin (1 nM, 8 h) on L-[(3)H]leucine incorporation in diabetic endothelial cells cultured in 5 mm D-glucose. 7. Human insulin reduced the elevated rates of L-arginine transport and cGMP accumulation in diabetic cells cultured in 5 mm D-glucose but failed to reduce increased rates of transport or NO production in cells exposed to 25 mm D-glucose or cycloheximide. 8. Our findings demonstrate that hyperglycaemia impairs the actions of human insulin on umbilical vein endothelial cells isolated from gestational diabetic pregnancies. Changes in insulin sensitivity and/or its signalling cascade may be affected by hyperglycaemia associated with gestational diabetes, resulting in insulin resistance in endothelial cells derived from the fetal vasculature.